Penataan Ruang Aceh Berbasis Islam dalam Negara Kesatuan Republik Indonesia - Arnita; Fikri (Puslatbang KHAN, 2022)
The Helsinki MoU agreement gave birth to Law Number 11 of 2006 concerning the Government of Aceh. In Article 171 Paragraph (1) of Law Number 11 of 2006 it states,